Time to listen: circadian impact on auditory research. Issue 18 (December 2020) - Cederroth, Christopher; Gachon, Frédéric; Canlon, Barbara
Abstract : There is accumulating experimental evidence that the peripheral and central auditory system is under circadian regulation, with both the cochlea and the inferior colliculus expressing rhythmic genes around the clock and differentially responding to noise trauma. In addition, time of the day also appears to impact the efficacy of drugs targeting the auditory system, with neurotrophic modulators having the opposite chronobiological profile of glucocorticoid agonists. Given how fundamental these basic biological mechanisms are in controlling auditory physiology, we propose that circadian aspects should be given greater attention in the auditory field. Taking circadian biology into account in the design of auditory experiments will not only help advance our understanding of the normal and abnormal function of this system, but it will also improve the design of drugs to prevent or treat hearing loss by adapting the timing of drug delivery to the auditory system.